2013
DOI: 10.1590/s1679-45082013000200013
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and functional capacity of elderly women with knee osteoarthritis

Abstract: Objective:To correlate functional ability and quality of life of elderly women with knee osteoarthritis.Methods:Cross-sectional study composed of 40 elderly women with knee osteoarthritis. We used the following instruments: identification questionnaire, Western Ontario and McMaster Universities Arthritis Index (WOMAC), and World Health Organization Quality of Life Questionnaire-OLD (WHOQOL-OLD). The significance level was 0.05 (5%), and confidence intervals were 95%. For statistical analysis we used parametric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
1
10

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 27 publications
2
17
1
10
Order By: Relevance
“…Alves and Bassitt10) found that half of their patients with OA reported intense or very intense pain when climbing up and down stairs and performing domestic tasks; a major portion of their patients complained of rigidity associated with moderate difficulty of physical function. They also described that the greatest reductions in QOL were strongly associated with the loss of FI10).…”
Section: Discussionmentioning
confidence: 99%
“…Alves and Bassitt10) found that half of their patients with OA reported intense or very intense pain when climbing up and down stairs and performing domestic tasks; a major portion of their patients complained of rigidity associated with moderate difficulty of physical function. They also described that the greatest reductions in QOL were strongly associated with the loss of FI10).…”
Section: Discussionmentioning
confidence: 99%
“…Degenerative knee arthritis is the most frequent chronic disease among the elderly aged 65 years or older. These patients suffer repeated cycles of worsening and relief of symptoms, which cause various physical and psychological problems 1) . Degenerative knee arthritis develops frequently in the synovial joints and is often accompanied by pathological changes such as damage to articular cartilage and osteophytosis, radiological changes such as narrowing of the joint cavity, joint pain, rigidity, limitation of movement, and joint friction.…”
Section: Introductionmentioning
confidence: 99%
“…15 Quanto aos pacientes que realizaram artroplastia de joelho, 73,3% apresentaram a artrose como principal mecanismo de lesão, diferindo dos estudos realizados 6,19 que evidencia a gonartrose. No entanto, a artrose é a queixa musculoesquelética mais comum, atingindo 10% da população mundial com idade acima de 60 anos, 20 influenciando na qualidade de vida, sobretudo nas mulheres, as quais possuem maior perda funcional, mais dor referida e maior comprometimento da qualidade de vida em relação aos homens da mesma faixa etária. 21 Na análise quanto ao tipo de artroplastia, 83,4% foram responsáveis pela substituição total do quadril e quanto ao tipo de prótese; 82,2% das artroplastias foram realizadas com a cimentada.…”
Section: Discussionunclassified